Effect of Logistic Support on Marketing Performance for Competitive Advantage - Muhamad Apep Mustofa; Nandan Limakrisna; Hari Muharam (Journal Research of Social Science, Economics, and Management, 2022)
An increasingly competitive business environment encourages high levels of competition and has a strong impact on marketing performance. Marketing performance plays an important role in business growth. Studies on marketing performance have been carried out by a number of researchers involving various variables including logistical support and the competitive advantage of a company. The logistical support and competitive advantage can identify marketing performance as a benchmark to remain competitive. The purpose of this study is to examine and analyze the effect of logistics support on competitive advantage, test and analyze the effect of logistics support on marketing performance, test and analyze the effect of competitive advantage on marketing performance, and test and analyze the effect of logistics support through competitive advantage on a company's marketing performance. The research method used is a quantitative approach using 25 samples consisting of staff, supervisors, and company managers under study. The results of the study indicate that there is a positive and significant direct effect of logistics support on marketing performance, and a positive and significant indirect effect of logistics support on marketing performance through competitive advantage.